PADEPOKAN SENI DAN BUDAYA MELAYU KALIMANTAN BARAT - Ikhsan, Muhammad; Khaliesh, Hamdil; Irwin, Irwin (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
Pontianak City has the potential for training and development of Malay cultural arts. The arts in West Kalimantan generally include dance, music, theater (folklore) and handicrafts. Special events in West Kalimantan will be the culmination of these arts and cultural performances, namely through festivals. This art can be used as a mainstay to face the ASEAN Economic Community. The final project of the Malay Art and Culture Hermitage of West Kalimantan aims to produce a special building design for Malay art and culture with the scope of cultural arts education, recreation, and tourism that can attract public interest. Design boundaries include the arts of music, dance, theater, crafts and cooking in West Kalimantan. The design method of the Malay Art and Culture Hermitage of West Kalimantan was carried out in several stages, namely ideas, data collection, identification, analysis, synthesis, and design development. The concept used in the design is based on the Facilities and Infrastructure Course and Training Institute Standards in 2017. Design analysis produces three functions, namely primary (education), secondary (administration, exhibition, performance) and tertiary (maintenance) functions. The result is that these three functions are combined in one into nine main buildings with a centralized organizational pattern of space, circular circulation, facades, and forms with Malay characteristics.